Who were the Burtases? - Yaroslav V. Pylypchuk (Историческая этнология, 2018)
This paper is devoted to the question of the Burtases ethnicity. The Burtases were originaly an Iranian-speaking population. They came to the Middle Volga region from the steppe and forest-steppe regions of Eastern Europe. The Burtases were not natives of the Middle Volga region. Burtases make alliances with the Khazars and helped them to installed the power of the Khazar Khanate over the Finnish nations of the Middle Volga. Burtases actively cooperated with its Turkic neighbors and subjected Turkization. Burtases was a heterogeneous population already in the Early Middle Ages, including Iranians and Volga Finns. Iranians occupied a dominant position; the Mordovians were also under their reign In the Late Middle Ages the people called Burtases became a Turkic speaking ethnic group.